Visa on Arrival Policy Against National Security - Purwanty, Yunishella; Daryanto, Eko (Syntax Corporation, 2024)
After the Covid-19 pandemic ended, there were changes in Indonesian immigration. The addition of visa on arrival subjects and the temporary suspension of visa-free visits is one way to restore the national economy. This research examines the impact of the visa on arrival policy on national security and analyzes whether this policy is still effective in the current era. This research uses a qualitative research type with literature study. From this research, the results show that immigration violations and the threat of transnational crime are still widespread after the latest visa on arrival policy was implemented, and in the current era, especially after the pandemic, there is a need for a capable system to provide immigration services as well as improve better security so that it can reduce threats and risks from violations committed by foreign nationals. The newly implemented e-VOA can be an effective innovation used in the current era to later replace manual VOA requests.